Effect of different intercropping systems on growth and yield of rose (Rosa indica) (Current Horticulture, 2024)
The field experiment was conducted to find out the effect of intercropping on annual rose (Rosa indica L.) cultivation at Floriculture Research Farm, ASPEE College of Horticulture and Forestry, Navsari Agricultural University, Navsari, during 2014-15. The intercrops were African marigold, French marigold and Gaillardia. The experiment was laid out in a randomized block design with 10 treatments. The vegetative parameters of rose were significant at different stages. The plant height was significant at the end of experiment. While at the end of first intercropping season, at the time of planting of second intercropping season and at the end of experiment plant spread was recorded significant. The highest yield was obtained from sole rose (6.79 tonnes/ha), while least was found in rose + gaillardia 1:2 (4.77 tonnes/ha). The highest rose equivalent yield (11.2 tonnes/ha) was observed from the treatment T2 (rose + African marigold 1:2). Whereas lowest (6.79 tonnes/ha) was recorded from the treatment T7 (rose sole). In view of the LER, highest value was recorded from intercropping rose + French marigold 1:2 (1.54). However, lowest value (1.0) was recorded from sole rose. This shows profitability of intercropping over the sole cropping.
Keywords: Rose; African marigold; French marigold; Gailardia; Intercropping systems; Growth; Plant height; Plant spread; Equilent yield etc